The structural and dynamic nanohardness properties of yttrium substituted layered (La, Ca)3Mn2O7 manganites - Koc, N. Soylu; Terzioglu, R.; Ozturk, O.; Terzioglu, C. (Springer Science and Business Media LLC, 2023)
This study devotes the structural and dynamic nanohardness properties of yttrium (Y) substituted within La1.4Ca1.6Mn2O7 manganites. XRD, SEM, EDS and dynamic nanohardness measurements are carried out to determine the structural properties such as grain sizes, impurity phases, crystallite sizes, average strain, and surface morphologies. The obtained results were compared with other rare-earth (RE) substituted double-layered lanthanum manganites published in the literature that have the same A-site radius. The lattice parameters are not affected substantially by the Y addition while the average grain size is significantly different from the other RE-substituted samples. The mechanical properties obtained from the dynamic micro-hardness tests such as the contact depth, area of the indent imprint, stiffness, creep, apparent hardness, reduced elastic modulus and the elastic recovery ratio (ERR) are calculated for the Y-substituted sample and compared with previously published studies. Different models are applied to determine the measured and true micro-hardness values. The microstructural and mechanical properties of Y-substituted double-layered manganites are discussed in detail.
Keywords: Physical-Properties; Instrumented Indentation; Magnetoresistance; Elastic Properties; Mechanical-Properties; Magnetic-Properties